Risk analysis factors for local recurrence in Ewing's sarcoma: when should adjuvant radiotherapy be administered?. (February 2018) - Albergo, J. I.; Gaston, C. L. L.; Parry, M. C.; Laitinen, M. K.; Jeys, L. M.; Tillman, R. M.; Abudu, A. T.; Grimer, R. J.
Abstract : Aims: The aim of this study was to analyse a group of patients with non-metastatic Ewing's sarcoma at presentation and identify prognostic factors affecting the development of local recurrence, in order to assess the role of radiotherapy. Patients and Methods: A retrospective review of all patients with a Ewing's sarcoma treated between 1980 and 2012 was carried out. Only those treated with chemotherapy followed by surgery and/or radiotherapy were included. Patients were grouped according to site (central or limb) for further analysis of the prognostic factors. Results: A total of 388 patients were included in the study. Of these, 60 (15%) developed local recurrence at a mean median of 27 months (sd 24, range 7 to 150) and the five-year local recurrence-free survival (5yrLRFS) was 83%. For central tumours, the size of the tumour and histological response to chemotherapy were found to be significant factors for local recurrence. For limb tumours, local recurrence was affected by intralesional and marginal resections, but not by the histological response to chemotherapy. Radiotherapy in those with a marginal resection reduced the risk of local recurrence (5yrLRFS: 96% versus 81%, p = 0.044). Conclusion: Local recurrence significantly affects the overall survival in patients with a Ewing's sarcoma. For those with a tumour in a limb, radiotherapy reduced the risk of local recurrence, especially in those with a marginal margin of excision, but the effect in central tumours was less clear. Radiotherapy for those who have had a wide margin of resection does not reduce the risk of local recurrence, regardless of the histological response to chemotherapy. Cite this article: Bone Joint J 2018;100-B: 247–55.